High Tumor Mitochondrial DNA Content Correlates With an Improved Patient's Outcome in WHO Grade III Meningioma - Hua, Lingyang; Juratli, Tareq A.; Zhu, Hongda; Deng, Jiaojiao; Wang, Daijun; Sun, Shuchen; Xie, Qing; Wakimoto, Hiroaki; Gong, Ye (Frontiers in Oncology, 2020)
Background: Studies have shown mitochondrial genome content (mtDNA content) varies in many malignancies. However, its distribution and prognostic values in high-grade meningioma remain largely unknown. In this retrospective study, we sought to assess a putative correlation between the mtDNA content and clinical characteristics. Methods: Mitochondrial DNA was extracted from 87 World Health Organization grade III meningioma samples using a qPCR method. The distribution of mtDNA content in WHO grade III meningioma and its correlations with clinical variables were assessed. Furthermore, we prognostic values were also determined. Results: Mean mtDNA content was 617.7 (range, 0.8–3000). There was no mtDNA distribution difference based on the histological subtypes (P = 0.07). Tumors with preoperative radiation were associated with lower mtDNA content (P = 0.041), whereas no correlations with other clinical variables were observed. A high mtDNA content was associated with significantly better PFS (P = 0.044) and OS (P = 0.019). However, in patients who received postoperative radiotherapy, low mtDNA content was associated with better PFS (P = 0.028), while no difference in OS was observed (P = 0.272). Low mtDNA content was also associated with better OS and PFS in subgroups of patients with ER negative status (PFS, P = 0.002; OS, P = 0.002). Conclusions: Consistent with other tumors, high mtDNA content was associated with better outcome in WHO grade III meningioma in our cohort. However, for patients who received post-operative radiation therapy, low mtDNA content was associated with better PFS. These findings suggest that mtDNA content may further be explored as a potential biomarker for high-grade meningioma patients and for those who received postoperative radiation therapy.